The Influence of Proportion Dominance and Global Need Perception on Donations - Ein-Gar, Danit; Give’on, Amir (Frontiers in Psychology, 2022)
Many donation-raising platforms request that first-time donors choose the charitable causes they most care about so that future campaign recommendations can best match donors' charitable preferences. While matching charitable campaigns to donors' reported preferences has its benefits little is known about other effects that choosing charitable causes may evoke. In this study, we focus on an overlooked aspect of choosing charitable causes, which is the effect of the number of charitable causes donors choose on their subsequent charitable behavior. We show in field and lab settings that the number of charitable causes donors choose as important to them increases their subsequent willingness to support a campaign; however, it does not influence their donation amount. We further show that the number of charitable causes chosen drives donors' global neediness perception. As the number of causes donors choose increases, donors experience an escalation in their perception of global neediness, which in turn motivates their willingness to support a campaign. However, global neediness perception does not motivate donors to donate greater amounts. The effect of the number of charitable causes chosen on willingness to support a campaign is observed while controlling for donors’ inherent prosocial attitudes toward helping.